Phthiria vaganoides sp. nov. (Bombyliidae, Phthiriinae, Phthiriini) from Northern Iran with the first record of Phthiria fulva Meigen, 1804 reared from a lepidopteran and description of the pupa - Gharali, Babak; Evenhuis, Neal (Zootaxa, 2017)
Based on material collected from Northern Iran, a new species of the genus Phthiria, Phthiria vaganoides sp. nov., is described and its diagnostic characters are photographed. Phthiria fulva Meigen, 1804 is also recorded for the first time from Iran. The pupal exuviae of Phthiria fulva Meigen is described and illustrated and its host, Argyresthia sp. is recorded. This marks the first description of an immature stage of the genus Phthiria.